Fiscal Reforms, Long-term Growth and Income Inequality - Acosta Ormaechea, Santiago (IMF Working Papers; Working Paper ;, 2017)
We estimate the effects on growth of nine fiscal reform episodes in seven high-income countries using the Synthetic Control Method. These episodes are selected using an indicator-based approach applied to the evaluation of growth-friendly fiscal reforms during 1975-2010. We find that in reform countries the annual growth rate of real GDP was on average about 1 percentage point above their synthetic units 10 years after each respective reform. Moreover, countries which were initially less developed seemed to experience a larger growth impact after their reforms. Results are broadly robust to controlling for structural reforms on business regulation, financial market, labor market, and legal and product markets, which may also affect growth. Our findings also suggest that inequality is not affected by the growth-friendly fiscal reforms analyzed in this paper.